2018
DOI: 10.1590/1516-3180.2017.0211061217
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of food outlets and intake of minimally processed and ultra-processed foods among 7 to 14-year-old schoolchildren. A cross-sectional study

Abstract: Use of butchers was associated with higher intake of unprocessed/minimally processed foods while use of snack bars or fast-food outlets may have a negative impact on schoolchildren's dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…Both studies detected associations between food environment characteristics and weight status. In Juiz de Fora, an inverse association was found between the density of supermarkets and hypermarkets and the prevalence of obesity 15 , while in Florianópolis, adolescents' families that used "public markets and greengrocers" and had restaurants near residences presented higher likelihoods to be overweight or obese 32 . A national schoolbased survey investigated the food environment in schools and found that schools that offered meals prepared on the school premises had lesser obesity rates for students 33 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Both studies detected associations between food environment characteristics and weight status. In Juiz de Fora, an inverse association was found between the density of supermarkets and hypermarkets and the prevalence of obesity 15 , while in Florianópolis, adolescents' families that used "public markets and greengrocers" and had restaurants near residences presented higher likelihoods to be overweight or obese 32 . A national schoolbased survey investigated the food environment in schools and found that schools that offered meals prepared on the school premises had lesser obesity rates for students 33 .…”
Section: Discussionmentioning
confidence: 92%
“…Several studies on adult populations have demonstrated positive associations between exposure to fast foods outlets and weight gain 28,29,30,31 . There is a paucity of studies on children and adolescents in this context, but research has rapidly been increasing in Brazil 15,16,32 . However, the methodology used to assess food environment varies between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive association between sugar-sweetened beverage consumption and the use of fast-food restaurants was also identified in Chinese adolescents [ 40 ]. We previously observed a positive association between the use of fast-food restaurants and the consumption of ultra-processed foods with the same characteristics of food groups found in the “Fast Food” pattern [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…Details on the sampling and design of the project were reported by previous studies [ 23 , 24 ]. In summary, a clustered sampling process was performed where the schools were divided into strata according to the administrative regions of the municipality of Florianópolis (central, north, east, and south island and mainland), and the type of school (public or private).…”
Section: Methodsmentioning
confidence: 99%